The Relationships between Behavioural Categories and Social Influences in the Gregarious Big Brown Bat (Eptesicus fuscus). (13th January 2013) - Kilgour, R. Julia; Brigham, R. Mark
Abstract: Behavioural plasticity is a critical component of natural selection leading to evolution. However, a surge of studies in the last two decades has discovered a distinct limit to behavioural plasticity, commonly referred to as behaviour types and behavioural syndromes. We set out to understand the relationships across behavioural categories in wild‐caught adult, female big brown bats and how they compare between social and solitary behaviours. Using bats sampled from four different maternity colonies, we ran a series of behavioural assays to create a behavioural profile for each individual. The behavioural profile encompassed exploratory, learning, competitive and aggressive categories. We found that Big brown bats exhibit a mean profile relatively unique to other well‐documented species, where aggression was linked to increased competitive ability but not to boldness. Our results indicate that the solitary and socially directed behaviours of individuals are not necessarily related and that behaviours pertaining to social interactions are linked most closely to learning abilities. Furthermore, we found evidence that poor body condition may be a predictor of increased social interactions and that behaviours exhibited in the presence of conspecifics are unrelated to those exhibited in solitude. These findings indicate importance of social affiliations on individual behaviours in this species and their uniqueness relative to other well‐studied taxa.